Penerapan Aromaterapi Chamomile Terhadap Kecemasan Pasien Pre-Pci di Rumah Sakit Abdul Moeloek Bandar Lampung - Richta Puspita Haryanti; Arief Shofyan Baidhowy; Sandra Andini; Prima Trisna Aji (Malahayati Nursing Journal, 2026)
ABSTRACT Coronary heart disease is one of the leading causes of mortality worldwide. Patients with ST-Elevation Myocardial Infarction (STEMI) who are scheduled to undergo Percutaneous Coronary Intervention (PCI) often experience high levels of anxiety, which may worsen hemodynamic conditions and compromise clinical stability. One potential intervention to address this issue is the administration of chamomile aromatherapy. To analyze the effect of chamomile aromatherapy on anxiety levels in patients during the preoperative phase of PCI at Abdul Moeloek Hospital, Bandar Lampung. This study employed a quasi-experimental design with a pretest-posttest approach. A total of 10 respondents were selected using purposive sampling. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI). The intervention consisted of inhalation of chamomile aromatherapy for approximately 8 hours at night over a period of three days. The study was conducted from January 25 to February 20, 2026. The findings showed that the mean anxiety score decreased from 44.60 to 34.80. Paired t-test analysis indicated a statistically significant difference (p = 0.000). Chamomile aromatherapy is effective in reducing anxiety levels among patients undergoing PCI in the preoperative phase. Keywords: Chamomile Aromatherapy, Anxiety, STEMI, PCI, Coronary Heart Disease.  ABSTRAK Penyakit jantung koroner termasuk salah satu penyebab utama kematian di dunia. Pasien dengan STEMI yang akan menjalani tindakan PCI sering mengalami kecemasan tinggi yang dapat memperburuk kondisi hemodinamik dan mengganggu stabilitas klinis pasien. Salah satu intervensi untuk mengatasi itu adalah dengan pemberian aromaterapi chamomile. Untuk menganalisis pengaruh aromaterapi chamomile terhadap tingkat kecemasan pasien pada fase preoperatif PCI di RS Abdul Moeloek Bandar Lampung. Desain penelitian menggunakan quasi-eksperimental dengan pendekatan pretest-posttest. Sampel sebanyak 10 responden dipilih secara purposive sampling. Pengukuran kecemasan menggunakan State-Trait Anxiety Inventory (STAI). Intervensi diberikan berupa inhalasi aromaterapi chamomile selama ±8 jam pada malam hari selama 3 hari. Periode penelitian berlangsung antara 25 Januari 2026 – 20 Februari 2026. Hasil penelitian menunjukkan rata-rata skor kecemasan menurun dari 44,60 menjadi 34,80. Uji paired t-test menunjukkan hasil signifikan (p = 0,000). Aromaterapi chamomile efektif dalam menurunkan kecemasan pasien preoperatif PCI. Kata Kunci: Chamomile Aromatherapy, Kecemasan, STEMI, PCI, Penyakit Jantung Koroner.